Item Analysis of Insya’ Assessment Based on Bloom’s Taxonomy at Islamic Senior High School Darussalam Rajapolah Tasikmalaya - Cecep Sobar Rochmat; Fitri Masturoh; Fairuz Subakir; Zhulfa Halimatus Sadiah (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2025)
Despite the widespread use of Insya’ assessments in educational institutions, comprehensive evaluations of item quality covering validity, reliability, discrimination, difficulty, and cognitive levels based on Revised Bloom’s Taxonomy remain limited. Previous studies rarely integrate statistical analysis with cognitive classification, particularly in high school Arabic education. This study addresses that gap by analyzing ten Insya’ assessment items from Grade 12 students at Islamic Senior High School Darussalam Tasikmalaya. Data consisted of exam questions, student answers, and scores, supported by literature. Collection methods involved interviews, observation, and documentation, with analysis conducted using SPSS version 30. The results showed 80% of items were valid, with a reliability coefficient of 0.743. Discrimination analysis rated 30% very good, 40% good, 10% acceptable, and 20% poor. Difficulty analysis revealed that 10% of the items were difficult, 70% were moderate, and 20% were easy. Cognitive levels indicated 80% assessed Understanding (C2), 10% Applying (C3), and 10% Creating (C6), with only 10% categorized as higher-order thinking skills (HOTS). These findings highlight the need for improved item design that promotes higher-order thinking and aligns more effectively with cognitive learning goals.